EFEKTIVITAS RELAKSASI GENGGAM JARI DAN KOMPRES HANGAT TERHADAP INTENSITAS NYERI PERSALINAN KALA I FASE AKTIF DI WILAYAH KERJA PUSKESMAS PARUNGPANJANG BOGOR - Aprilia Rahayu, Elsa; Septa Rini, Ageng; Jayatmi, Irma (Berajah Journal, 2024)
Labor pain is often experienced by mothers giving birth. Finger grasp relaxation and warm compress techniques can be used to reduce the intensity of labor pain in the active phase of the first stage. This study aims to determine the effectiveness of these techniques in the Parungpanjang Community Health Center, Bogor, in 2024. This research is a quasi-experiment with a pretest-posttest control group design. The population was mothers in the active phase of labor. Samples consisted of 23 respondents in the intervention group and 23 in the control group. The instrument used was the Numeric Rating Scale (NRS). Data were analyzed using t-test and ANOVA. The results showed significant differences between the intervention and control groups. The intervention group experienced a greater reduction in pain intensity compared to the control group (p = 0.002).